Spatial distribution of Culicidae (Diptera) larvae, and its implications for Public Health, in five areas of the Atlantic Forest biome, State of Sao Paulo, Brazil - Piovezan, Rafael [UNESP]; Oliveira Acorinthe, Joao Paulo; Teixeira de Souza, Jonas Henrique; Visockas, Alexandre; Azevedo, Thiago Salomao de; Von Zuben, Claudio Jose [UNESP] (Soc Brasileira Entomologia, 2017)
In view of the adaptive ability of mosquitoes and their role in the transport of infective agents, entomological surveys undertaken in transitional environments are very important for the determination of the risk they represent for Public Health. Among the principal vectors of the infectious agents involved in the occurrence of important arboviruses, such as dengue, for example, are the Culicidae-insects capable of installing themselves in the urban nuclei, which exist within areas containing vestigial forests. This present study conducted a survey of mosquito species by means of traps to catch their larvae installed in five rural areas within the Atlantic Forest domain and containing its vestigial vegetation in the municipality of Santa Barbara D'Oeste, Sao Paulo, Brazil. A total of 13,241 larvae belonging to six mosquito species were collected on 920 occasions (32.52% of positive collections). Aedes albopictus (64.23%) and Aedes aegypti (32.75%) were the most frequent, followed by Culex quinquefasciatus (1.32%), Aedes fluvi-atilis (1.04%), Culex Complex Coronator (0.40%) and Toxorhynchites theobaldi (0.22%). Three areas were analyzed by means of Simpson's diversity index and the spatial analysis showed that the sites with the greatest abundance of Ae. aegypti presented lower diversity values and were associated with more highly consolidated urban nuclei. The vector of dengue, chikungunya and zika has great infesting ability in urban areas, which means that the early implementation of entomological surveillance and control activities in specific areas - such as transitional ones - is highly important. (C) 2017 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda.
Keywords: Aedes aegypti; Aedes albopictus; Dengue; Entomological surveillance; Spatial analysis